The profiling of morbidity and mortality at Kimberley military sickbay in South Africa, 2010-2019 - Makhavhu, Musiiwa (My University, 2021)
Background: Military jobs have in general put different and higher demands on the individual compared to most civilian jobs. Therefore, the nation’s armed forces depend on men and women who are fit, healthy, and able to perform at their peak on or off the battlefield however, potential recruits are not immune to the health problems that affect the rest of the population, and the impact on military readiness is substantial. The measurement of morbidity and mortality is important for several reasons and the resulting data provide a basis for generating hypotheses related to the aetiology of diseases; for determining the effectiveness of both preventive and treatment efforts; and for evaluating needs for specific health services, both clinical and preventive. Methodology: The aim of this study is to profile the mortality and morbidity in Kimberley Military Sickbay. A cross-sectional descriptive study design was used to help address the research question posed in this study. A retrospective quantitative research method was used because of its advantages and a link to the research purpose. The data was extracted from the military health database and 156 008 records were reviewed to investigate the profile of morbidity and mortality in Kimberly Military Sickbay, South Africa. Results: The mean age of the participants was 33.6 ±15.7 years, ranging from 1 year to 98 years old. Majority of the medical records were in the age group 24 – 44 years at 46.2% followed by those in age groups 45 – 64 years, 18 – 24 years, 0 – 9 years and 10 – 17 years at 25.4%, 11.6%, 10.4% and 4.9% respectively. The least medical records were in the age group 65 years and above at 1.5%. Most of records represented males at 57% and females at 43%. Race distribution of the medical records at Kimberly Military Sickbay showed that majority of medical records were for Blacks at 58.5% followed by Coloured, Whites and Asians at 26.2%, 14.3% and 1.0% respectively. Morbidity was recorded to be 11 564 in 2010 then increased to 12 067 in 2011. This decreased to 10 918, 8 665 and 8 593 in 2012, 2013 and 2014 respectively. Then morbidity increased from 11 417 in 2015 to 12 541 in 2019. Mortality was high in 2018 at 24.5% followed by 2019, 2010, 2015 and 2-17 at 19.1%, 16.5%, 13.3% and 11.8% respectively. The data shows that the highest ranking morbidity for all ages was upper respiratory infections followed by Injuries, pains malaise and fatigue; HIV/AIDS while Influenza & pneumonia ranked number ten (10). In age group 18 – 24 years the highest ranking morbidity was Injuries, pains malaise and fatigue followed by psychological evaluations and psychiatric conditions; upper respiratory tract infection and Influenza & pneumonia ranked number ten (10) as in all ages. HIV/AIDS ranked highest in age group 25 – 44 years followed by upper respiratory tract infection and Injuries, pains malaise and fatigue while Cellulitis, Dermatitis, fungal and skin infections ranked number ten (10). In age group 45 – 65 years the highest ranking morbidity was fevers followed by Blood and immune system conditions; cerebrovascular disease while Digestive tract conditions ranked number ten (10) The association of demographics with mortality revealed that older people (25 years and above) were 5.5 more likely to die as compared to younger people (≤ 24) at p-value= 0.001. Males were 2.7 times more likely to die as compared to women at p-value= 0.001 while Coloured were 0.8 times less likely to die as compared to Blacks at p-value= 0.001 and Whites were 1.3 times more likely to die as compared to Blacks at p-value= 0.001 and lastly Asians were 0.1 less likely to die as compared to Blacks at p-value= 0.001 Conclusion: This study gives a brief description of the health profile of patients attending the military training at Kimberley over a period. This knowledge would help in planning health services to meet the patient’s needs and help in training health staff. Many diseases have seasonal variation and the burden of these diseases can be reduce by steps taken by the health planners and manager beforehand and through implementation of surveillance program. This study concluded that the demographics of most soldiers were males as it is believed that soldiers must be fit and aggressive. It also revealed that the morbidity and mortality of soldiers in the base are in most cases the same as the other countries due to other studies done previously. The association of demographics with mortality shows that older people (25 years and above) were 5.5 more likely to die as compared to younger people (≤ 24) at p-value= 0.001. Males were 2.7 times more likely to die as compared to women at p-value= 0.001.
Thesis (MPH.) -- University of Limpopo, 2021
Keywords: Profiling; Morbidity; Mortality; Deseases -- Reporting; Occupational mortality; Military hygiene; Mortality